Calorimetric and Spectroscopic Studies of Water Adsorption onto Alkaline Earth Fluorides - Toshinori Mori; Yasushige Kuroda; Ryotaro Kumashiro; Koji Hirata; Hidehiro Toyota; Mahiko Nagao (Adsorption Science & Technology)
Interactions between the surfaces of alkaline earth fluorides (CaF 2 , SrF 2 and BaF 2 ) and water molecules were investigated by calorimetric and spectroscopic methods. The exposed surfaces of the alkaline earth fluoride samples, with which the (100) crystalline plane is mainly associated, were found to be fully covered with strongly adsorbed water molecules, resulting in characteristic IR bands at 3684, 2561, 1947 and 1000 cm −1 , respectively. This surface was homogeneous towards further water adsorption. The strongly adsorbed water molecules were almost completely desorbed from the surface on evacuating the sample up to 473 K. The heat of immersion in water also increased with increasing pretreatment temperature; this may be attributed to surface rehydration of the alkaline earth fluorides. The state of the surface changed drastically as the pretreatment temperature was increased and stabilized towards incoming water molecules. Thus, the surface formed after evacuation at temperatures greater than 473 K was resistant to hydration even after immersion in water at room temperature. This surface was relatively heterogeneous towards water adsorption, although it behaved homogeneously towards argon adsorption. These facts indicate that strongly adsorbed water molecules appear to be somewhat specific towards the adsorption of further incoming water molecules. The adsorption properties of the (100) plane of alkaline earth fluorides towards water and argon molecules depend strongly on both the electrostatic field strength and the extent of rehydration of the alkaline earth fluoride surface.